2021
DOI: 10.3390/polym13213839
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Antigenotoxic Effects of Alginate and ZnO/Alginate–Nanocomposites Extracted from Brown Alga Fucus vesiculosus in Mice

Abstract: Mitomycin C (MMC) is an alkylating chemotherapy drug that could induce DNA damage and genetic alteration. It has been used as a model mutagen for in vivo and in vitro studies. The current study aimed to evaluate the protective role of Zinc oxide alginate–nanocomposites (ZnO-Alg/NCMs) against MMC–induced genotoxicity in mice. Animals were treated as follows: the control group, the groups treated with Algin (400 mg/kg b.w), the groups treated with ZnO-Alg/NCMs (400 mg/kg b.w), the group treated with MMC, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Furthermore, this antioxidant property is vital in preventing generation of free radicals in cell, which prevents oxidative cell wall damage [31]. The antigenotoxic property of alginate oligosaccharide in form of nanocomposites extracted from brown alga has received significant attention [32]. Table 1 shows some of the activities and qualities of polysaccharides from seaweeds that are useful as antioxidants and anticancer agents.…”
Section: Role Of Polysaccharides In Medicinementioning
confidence: 99%
“…Furthermore, this antioxidant property is vital in preventing generation of free radicals in cell, which prevents oxidative cell wall damage [31]. The antigenotoxic property of alginate oligosaccharide in form of nanocomposites extracted from brown alga has received significant attention [32]. Table 1 shows some of the activities and qualities of polysaccharides from seaweeds that are useful as antioxidants and anticancer agents.…”
Section: Role Of Polysaccharides In Medicinementioning
confidence: 99%
“…The alginate extracted from F. vesiculosus was according to the methods of Hambali et al [ 31 ]. The F. vesiculosus alginate was characterized according to previous research by Hamouda et al [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Strojny-Cieślak [53] reported that graphene oxide-silver and graphene oxide nanoparticles had high cytocompatibility toward human cell lines, fetal foreskin fibroblasts (HFFF2), and lung epithelial cells (A549). ZnO-Alginate/NCMs induced significant protection against Mitomycin C (MMC) [54]. Salman et al [55] reported the oral treatment with Chitosan Nanoparticles (CNPs), and their loaded Capparis cartilaginea Decne extract, is safe; the chitosan nanoparticles exhibited powerful antigenotoxic properties.…”
Section: Evaluation Of In Vitro Hepatoprotective Activitymentioning
confidence: 99%